Capstone curriculum across disciplines : a snapshot of current practice in Australia and beyond : survey report. - Lee, Nicolette; Loton, Daniel John (Office for Learning and Teaching, 2015)
This report presents the results of an international survey on capstones in higher education. At the commencement of this study, anecdotal evidence and international research suggested capstones are delivered using a diverse range of curriculum approaches such as project or problem-based learning, the involvement of external industry or community partners, placements, simulations or portfolios. Length, delivery mode and assessment style and scope also vary significantly. The aim of the survey was to provide a broad empirical overview of how capstones are structured and delivered, as well as participant perceptions of factors impacting their effectiveness and the benefits and challenges they present. For the purposes of the survey, a capstone was defined very broadly as: 'a significant, culminating and assessed learning experience within a qualification, although it may also be non-credit bearing. Capstones are likely to implicitly or explicitly focus on providing students with an opportunity to integrate and apply prior learning, and to support the transition to professional life or post-graduate studies. It may be called a capstone, a final year project or dissertation, depending on the country and nature of the curriculum'.